Bench-to-bedside review: Rare and common viral infections in the intensive care unit – linking pathophysiology to clinical presentation - Stollenwerk, Nicholas (BioMed Central, 2008)
Viral infections are common causes of respiratory tract disease in the outpatient setting but much less common in the intensive care unit. However, a finite number of viral agents cause respiratory tract disease in the intensive care unit. Some viruses, such as influenza, respiratory syncytial virus (RSV), cytomegalovirus (CMV), and varicella-zoster virus (VZV), are relatively common. Others, such as adenovirus, severe acute respiratory syndrome (SARS)-coronavirus, Hantavirus, and the viral hemorrhagic fevers (VHFs), are rare but have an immense public health impact. Recognizing these viral etiologies becomes paramount in treatment, infection control, and public health measures. Therefore, a basic understanding of the pathogenesis of viral entry, replication, and host response is important for clinical diagnosis and initiating therapeutic options. This review discusses the basic pathophysiology leading to clinical presentations in a few common and rare, but important, viruses found in the intensive care unit: influenza, RSV, SARS, VZV, adenovirus, CMV, VHF, and Hantavirus.